Secondary Syphilis with Eosinophilia Complicated by Severe Jarisch–Herxheimer Reaction - Elias, Anthony (Case Rep Infect Dis, 2020)
It has long been acknowledged that syphilis is a disease with a diverse range of presentations. We herein describe a case of a young man who presented with fever, rash, and eosinophilia following the commencement of allopurinol, only to be diagnosed with secondary syphilis on histopathology. His treatment was complicated by a severe exacerbation of his cutaneous eruption following the commencement of penicillin, likely secondary to a Jarisch–Herxheimer reaction, an entity often overlooked by clinicians managing syphilis.